Illocutionary Act Analisys Of The Main Character In Emancipation Movie And Its Contribution In Teaching Speaking - Maulana Yusuf Mahendra; Suwandi Suwandi; Fitri Yulianti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
In this research, the main focus is on illocutionary acts in the movie